2022
DOI: 10.3390/ijms23116072
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Alleviates Short-Term Lincomycin-Induced Intestinal and Liver Injury and Inflammation in Infant Mice

Abstract: The adverse effects of short-term megadose of antibiotics exposure on the gastrointestinal and liver tissue reactions in young children have been reported. Antibiotic-induced intestinal and liver reactions are usually unpredictable and present a poorly understood pathogenesis. It is, therefore, necessary to develop strategies for reducing the adverse effects of antibiotics. Studies on the harm and rescue measures of antibiotics from the perspective of the gut–liver system are lacking. Here, we demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The reciprocal crosstalk among gut microbiota, lipid metabolism, and Th1/Th2/Th17 cells further amplifies the inflammatory response. 76 For instance, pro-inflammatory cytokines secreted by Th1/Th17 cells can perpetuate dysbiosis, whereas the dysbiotic gut microbiota can promote the polarization of Th1/Th17 cells and impair In our subsequent research, we aim to elucidate the specific mechanisms by which G-Rg1 targets the effector function of Th1/Th2/Th17 cells depending on the gut microbiota. First, we plan to establish a pseudogerm-free mouse model by using antibiotics to clear the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reciprocal crosstalk among gut microbiota, lipid metabolism, and Th1/Th2/Th17 cells further amplifies the inflammatory response. 76 For instance, pro-inflammatory cytokines secreted by Th1/Th17 cells can perpetuate dysbiosis, whereas the dysbiotic gut microbiota can promote the polarization of Th1/Th17 cells and impair In our subsequent research, we aim to elucidate the specific mechanisms by which G-Rg1 targets the effector function of Th1/Th2/Th17 cells depending on the gut microbiota. First, we plan to establish a pseudogerm-free mouse model by using antibiotics to clear the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dysregulated immune responses mediated by Th1/Th2/Th17 cells contribute to the pathogenesis of both UC and obesity. , Th1/Th17 cells secrete IFN-γ, and IL-17A, driving mucosal inflammation in UC, while Th2 cells secrete IL-4 to promote tissue repair. The reciprocal crosstalk among gut microbiota, lipid metabolism, and Th1/Th2/Th17 cells further amplifies the inflammatory response . For instance, pro-inflammatory cytokines secreted by Th1/Th17 cells can perpetuate dysbiosis, whereas the dysbiotic gut microbiota can promote the polarization of Th1/Th17 cells and impair Th2 cell function, exacerbating inflammation and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, baicalin (12.5 µM and 25 µM) was found to effectively inhibit the expression of ER stress marker phosphorylated inositol-requiring enzyme 1α (p-IRE1α) and reverse palmitic acid (PA)-induced apoptosis and reactive oxygen species (ROS) production [38]. The main mechanism might be because baicalin reduced PA-induced cytotoxicity by inhibiting ER stress and the activation of thioredoxin-interacting protein (Txnip)/NLRP12 inflammasome [39]. These studies provide a new theoretical basis for the clinical application of baicalin and further improve the cytotoxicity study of baicalin.…”
Section: Toxicity Of Baicalinmentioning
confidence: 99%
“…Baicalin (BA) is among the most potent and plentiful flavonoids extracted from Scutellaria baicalensis, and its chemical structure is shown in Figure 1B . Previous studies have shown that BA has antioxidant ( Shi et al, 2018 ), anti-inflammatory ( Zhang et al, 2022 ), anti-apoptosis ( Zhao et al, 2022 ), antiviral ( Zhao et al, 2018 ) and other effects. Recently, there has been an increasing focus on its ability to protect against liver and intestinal tract diseases ( Liao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, BA may control enteric-related disorders and protect the intestine against sepsis and ulcerative colitis ( Zhu et al, 2020 ). Several trials have also proven BA to alleviate liver disease through the hepatointestinal axis ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%